2021
DOI: 10.1111/evj.13406
|View full text |Cite
|
Sign up to set email alerts
|

Rational dosage regimens for cephalothin and cefazolin using pharmacokinetics and pharmacodynamics analysis in healthy horses

Abstract: Background: First-generation cephalosporins have good activity against gram-positive bacteria and are extensively used in horses. There are few reports of pharmacokinetics and pharmacodynamics (PK/PD) analysis of cephalosporins in horses.Objective: To optimise the dosages of the two first-generation cephalosporins cephalothin (CET) and cefazolin (CEZ) in horses using PK/PD concepts.Study design: Experimental study with single administration.Methods: Drug plasma concentrations following a single intravenous (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 34 publications
3
26
0
Order By: Relevance
“…Thus, CET administration twice or three times a day could control gram-positive bacteria that were frequently isolated from horses with cellulitis [6]. Administration of CET every 6-12 hr resulted in a high cure rate (94.7%) in 3,292 horses with limb infections [9]; our results for the CET concentrations in subcutaneous and hoof tissues are in line with the effectiveness of CET for treating limb infections.…”
supporting
confidence: 80%
See 4 more Smart Citations
“…Thus, CET administration twice or three times a day could control gram-positive bacteria that were frequently isolated from horses with cellulitis [6]. Administration of CET every 6-12 hr resulted in a high cure rate (94.7%) in 3,292 horses with limb infections [9]; our results for the CET concentrations in subcutaneous and hoof tissues are in line with the effectiveness of CET for treating limb infections.…”
supporting
confidence: 80%
“…This study considered the treatment of infectious diseases at different sites in horses by evaluating CET concentrations in body fluids and tissue samples in adult Thoroughbred horses and the MIC 90 values of bacteria isolated from Thoroughbred racehorses with infectious diseases, including pneumonia and cellulitis, at two training facilities (Ritto and Miho training centers) in a previous report [9]. CET concentrations or MICs of bacteria may be different between this In this study, CET showed good penetration into body fluids, and a dose of 22 mg/kg twice a day was effective for septic arthritis, pleuritis, and peritonitis caused by grampositive bacteria but ineffective for osteomyelitis due to an insufficient bone concentration.…”
mentioning
confidence: 99%
See 3 more Smart Citations